Decrease in visual acute, hypertellorism, and exophthalms due to bilateral piomucocele - Vergara-de la Rosa, Esteban (2021)
Background: The Piomucocele is the infection of a pre-existing mucocele. We present a 22-year-old man with decreased visual acuity, hypertelorism,andexophthalmos.Hepresentedinferolateral proptosis and visual acuity 20/80 on the left side. No history of trauma, infection, polyps, or surgery. CTscan with images suggestive of bilateral mucocele with anterior orbital compression effect on the right side and posterior on the left side. The compressive effect of the ethmoidal and sphenoid pyomukocele on the left side produced compromise of the optic canal with decreased ipsilateral visual acuity. Endoscopic sinonasal surgery was performed with marsupialization and decompression,findingtwowell-definedanteroposterior pyomukoceles on the right side and one left pyomukocele. The evolution was favorable. This unusual presentation forces us to consider unsuspected ocular involvement, mainly in pyomukoceles that involve posterior paranasal sinuses.